HUBUNGAN KEKERABATAN Shorea gysbertsiana DENGAN TIGA JENIS Shorea PENGHASIL TENGKAWANG LAINNYA BERDASARKAN PENANDA RAPD - Purnamila Sulistyawati; AYPBC Widyatmoko (Jurnal Pemuliaan Tanaman Hutan, 2018)
The Shorea tengkawang species; Shorea pinanga, S. stenoptera, S. macrophylla and S. gysbertsiana known for their high-value wood and non-wood products. Shorea tengkawang produces tengkawang oil which usually used as a raw material and supporting material for the manufacture of food, pharmaceuticals and cosmetics. This study determines the genetic relationship of S. gysbertsiana to another three Shorea species uses RAPD (Random Amplified Polymorphism DNA) specific loci. There were 13 specific alleles obtained from 6 RAPD primers. Among these specific alleles, there were 8 loci shared between S. gysbertsiana and S. macrophylla, and 2 loci shared with S. stenoptera.  There were no specific loci shared between S. gysbertsiana and S. pinanga. This study found one specific locus for S. gysbertsiana and one specific locus between S. stenoptera and S. pinanga. These results revealed a very close genetik relationship of S. gysbertsiana to S. macrophylla and S. stenoptera.The specific loci found in this study can be used to support the morphological identification, also for supporting conservation program of these four Shorea species.